2019
DOI: 10.3389/fped.2018.00412
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Prevalence, Demographics, and Costs of ME/CFS Using Large Scale Medical Claims Data and Machine Learning

Abstract: Techniques of data mining and machine learning were applied to a large database of medical and facility claims from commercially insured patients to determine the prevalence, gender demographics, and costs for individuals with provider-assigned diagnosis codes for myalgic encephalomyelitis (ME) or chronic fatigue syndrome (CFS). The frequency of diagnosis was 519–1,038/100,000 with the relative risk of females being diagnosed with ME or CFS compared to males 1.238 and 1.178, respectively. While the percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 18 publications
6
98
0
2
Order By: Relevance
“…We observed a high heterogeneity in the reported prevalence; as estimated, the ranges for three extraction methodologies were 1.40% (95% CI: 0.98-1.82) for the averaged prevalence, 0.39% (95% CI: 0.00-0.81) for the pooled prevalence and 0.68% (95% CI: 0.48-0.97) for the metaanalysis. Recently, one study reported a 0.67% CFS or ME prevalence and a 0.12% ME prevalence using large medical claims data with ICD (International Classification of Disease) codes [61]. Those results concur with our CFS/ ME prevalence findings of 0.68% for the entire dataset and 0.09 and 0.12% in the meta-analysis based on physician diagnosis and the Holmes definition, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed a high heterogeneity in the reported prevalence; as estimated, the ranges for three extraction methodologies were 1.40% (95% CI: 0.98-1.82) for the averaged prevalence, 0.39% (95% CI: 0.00-0.81) for the pooled prevalence and 0.68% (95% CI: 0.48-0.97) for the metaanalysis. Recently, one study reported a 0.67% CFS or ME prevalence and a 0.12% ME prevalence using large medical claims data with ICD (International Classification of Disease) codes [61]. Those results concur with our CFS/ ME prevalence findings of 0.68% for the entire dataset and 0.09 and 0.12% in the meta-analysis based on physician diagnosis and the Holmes definition, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, case definition and diagnostic methods are the factors with the greatest influence on the results, with data ranges that vary by approximately 5-to tenfold. Following our study results, in addition to a proposal for a new diagnostic code [61,62], a pattern recognition methods to subdivide CFS patients according to symptom clusters (e.g., specific phenotype features) with the adaption of objective measurement (e.g., two cardiopulmonary exercise tests, CPETs) were suggested for more empiric definition of the condition [44].…”
Section: Discussionmentioning
confidence: 99%
“…Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a perplexing disease, silently destroying millions of lives. Indeed, the latest prevalence rate of ME/CFS estimates that there are over 65 million suffering individuals throughout the world [1], and 35-40% of patients are male. Thus, while women are more often diagnosed, the disease is by no means rare in males.…”
Section: Introductionmentioning
confidence: 99%
“…These misconceptions can lead to all sorts of problems for patients including the refusal of benefits or medical retirement. ME/CFS is not a rare disease [8] and it represents a considerable public health burden with an estimated annual total value of direct and indirect economic costs to society in the US of $17 to $24 billion, including $9.1 billion attributed to lost productivity [9].…”
Section: Introductionmentioning
confidence: 99%